PEMBANGUNAN MASYARAKAT YANG MENGABDI DAN BERKELANJUTAN MELALUI PROGRAM KESEHATAN, PENDIDIKAN, LINGKUNGAN, DAN PENGEMBANGAN FASILITAS - Gunawan, Ivan Andri; Nurliasari, Suci; Luiz Figo Resda, Valentino; Fernando T, Franky; Lugianus Andika Roy, Steven; Yohanes, Vian; Asmara, Gita; Imelda; Rinaldi, Aldy; Gibran, Kholil; Arista Purnama, Rifky; Adrian Pane, Gandi; Laiy, Victorianus; Suci Anugrah, Adis; Ivanda, Riko; Pernanda, Perdi; Yunita, Dwi; Hendra, Adesius; Aprella, Vena (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
The Community Service Program (KKN) in Rasau Jaya Dua Village, Rasau Jaya Subdistrict, Kubu Raya Regency, West Kalimantan, was conducted under the theme “Independent and Sustainable Development through Health, Education, Environment, and Village Facility Development Programs.” This program aimed to address key issues faced by the community, particularly in the areas of environment, education, and limited supporting facilities. The main activities included areca nut tree planting to prevent abrasion and preserve the environment, an anti-bullying campaign for elementary school students, a financial literacy program to encourage saving habits, and group exercise activities to promote health and physical fitness. In education, study groups were organized for elementary school students (grades 1–6) to enhance learning motivation and academic performance. Additionally, the program contributed to village development through the installation of cemetery signboards and papaya cultivation to support local economic benefits. The implementation of all activities was supported by village officials and community participation, resulting in positive impacts such as increased environmental awareness, improved educational quality, and the promotion of sustainable village development.